Paradise, New York : a novel - Pollack, Eileen, 1956- (Temple University Press, 1998)
A young Jewish woman drops out of college to run her family's rundown hotel in the Catskills. The novel describes the hotel's multicultural characters, among the staff and the guests, and her romance with a black handyman.